Peningkatan Kemampuan Membaca Pemahaman Pada Mata Pelajaran Bahasa Indonesia Melalui Media Buku Cerita Bergambar Siswa Kelas II SDN 003 Loa Janan Ilir - Farida Maulida; Nanda Shaqinah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the implementation of picture book media and to determine the improvement in reading comprehension skills of second-grade students at SDN 003 Loa Janan Ilir through the use of picture books in Indonesian language learning. This research employs a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, implemented in two cycles. The research subjects consisted of 25 second-grade students at SDN 003 Loa Janan Ilir for the 2024/2025 academic year. Data collection techniques included reading comprehension tests, classroom observation of teacher and student activities, and semi-structured interviews with the class teacher. Results demonstrated significant improvement in students' reading comprehension. In the pre-cycle phase, the class average was only 54.6 with a classical mastery rate of 20.0%. After Cycle I, which employed a read-aloud strategy using the story